Why do the young generations not play golf? - Portugal, Miguel Nuno (2021)
Golf is one of the most competitive sports for tourists in Portugal but not among the young generation. The young population often neglected this sport and categorized it as an elite sport for seniors. This situation may compromise the position Portugal has of the best golf destination in the world. To keep this position it is time to promote and attract young people starting with the residents. This research, exploratory in its essence, used a convenience sample to test why young people do not feel attracted to practice golf. The results suggest that there are very few teenagers willing to practice golf. The arguments are mostly this sport is not affordable, it is more tourist oriented, and is connoted as an eclectic social activity more than as a sport. These results, with evident implications on the attractiveness of golf, suggest that to overcome this situation the promotion should be oriented to attract young people.